Musculoskeletal Injury Risk in a Military Cadet Population Participating in an Injury-Prevention Program - Ivar Vähi; Leho Rips; Ahti Varblane; Mati Pääsuke (Medicina, 2023)
Background and Objectives: Musculoskeletal injuries are a major health hazard among military personnel. Previous research has proposed several exercise-based strategies for prevention. The purpose of this study was to investigate the effect of an exercise-based injury-prevention program on the incidence of musculoskeletal injury, motor performance and psychosocial status. Materials and Methods: Thirty-six Estonian Military Academy cadets were randomly assigned into either an intervention or control group. The intervention group followed a neuromuscular exercise-based injury-prevention warm-up program, three times per week for 6 months. The control group continued with the usual warm-up. The main outcome measure was injury incidence during the study period. Additionally, evaluation of isokinetic lower-extremity strength, postural sway, physical fitness and psychosocial status was included pre- and post-intervention. Results: During the 6-month study period, the musculoskeletal injury incidence was 43% in the intervention group and 54% in the control group (RR = 0.8; 95% CI = 0.41 to 1.99). The noted 20% risk reduction was not statistically significant (p = 0.59). Furthermore, there were no statistically significant differences between the intervention and control group in motor performance or psychosocial status measures. Conclusions: In conclusion, no effect of the exercise-based injury-prevention program on injury risk, motor performance or psychosocial status could be detected.